Corticospinal excitability during motor imagery is reduced in young adults with developmental coordination disorder. (January 2018) - Hyde, C.; Fuelscher, I.; Williams, J.; Lum, J.A.G.; He, J.; Barhoun, P.; Enticott, P.G.
Abstract: While a compelling body of behavioral research suggests that individuals with developmental coordination disorder (DCD) experience difficulties engaging motor imagery (MI), very little is known about the neural correlates of this deficit. Since corticospinal excitability is a predictor of MI proficiency in healthy adults, we reasoned that decreased MI efficiency in DCD may be paralleled by atypical primary motor cortex (PMC) activity. Participants were 29 young adults aged 18- 36 years: 8 with DCD (DCD) and 21 controls. Six participants with DCD and 15 controls showed behavioral profiles consistent with the use of a MI strategy (MI users) while performing a novel adaptation of the classic hand laterality task (HLT). Single-pulse transcranial magnetic stimulation (TMS) was administered to the hand node of the left PMC (hPMC) at 50 ms, 400 ms or 650 ms post stimulus presentation during the HLT. Motor-evoked potentials (MEPs) were recorded from the right first dorsal interosseous (FDI) via electromyography. As predicted, MI users with DCD were significantly less efficient than MI using controls, shown by poorer performance on the HLT. Importantly, unlike healthy controls, no evidence of enhanced hPMC activity during MI was detected in our DCD group. Our data are consistent with the view that inefficient MI in DCD may be subserved by decreased hPMC activity. These findings are an important step towards clarifying the neuro-cognitive correlates of poor MI ability and motor skill in individuals with DCD.